Determinants for worsening in systemic autoimmune rheumatic disease-associated interstitial lung disease: a systematic review and meta-analysis of cohort studies - Yao, Jiaheng; Wang, Jun; Guo, Luhan; Su, Peipei; Li, Jiansheng; Li, Bin (Frontiers in Medicine, 2024)
Background: To identify risk factors for progression, acute exacerbation (AE), and the development of rapidly progressive interstitial lung disease (RP-ILD) in Systemic autoimmune rheumatic disease-associated interstitial lung disease (SARD-ILD). Methods: We systematically searched PubMed, EMBASE, Scopus, the Cochrane Library, and Web of Science databases to identify eligible cohort studies up until Jan. 01, 2024. Two reviewers independently screened the literature and extracted data. We employed the Newcastle-Ottawa Scale (NOS) to assess study quality and performed meta-analyses using STATA software. Results: This review included 50 studies. For progression, 28 studies were included, 4 significant risk factors were identified: male (OR=1.97, 95% CI 1.26-3.08, p<0.001), UIP patterns on HRCT (OR=1.94, 95% CI 1.48-2.54, p<0.001), extensive lung involvement (OR=2.15, 95% CI 1.66-2.80, p<0.001), and age (OR=1.07, 95% CI 1.05-1.10, p<0.001); and 11 potential risk factors. 7 studies were included in AE, and 3 potential risk factors were highlighted: FVC, UIP patterns on HRCT, and smoking history. In RP-ILD, 15 studies were included. 3 risk factors were determined: High CRP (OR=2.45, 95% CI 1.87-3.21, p<0.001), Ro-52 positivity (OR=5.35, 95% CI 3.46-8.29, p<0.001), and MDA5 antibodies (OR=2.09, 95% CI 1.47-2.95, p<0.001); along with 10 potential risk factors. Conclusion: Our meta-analysis identified male sex, UIP pattern on HRCT, extensive lung involvement, and advanced age as significant risk factors for the progression of SARD-ILD. High CRP, Ro-52 positivity, and MDA5 antibodies were significant risk factors for developing of RP-ILD in patients with IIM. We also discovered several potential risk factors that may be associated with the progression of SARD-ILD and acute exacerbation, as well as the occurrence of RP-ILD in IIM patients.